2019
DOI: 10.1002/ece3.5733
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary survey of medium and large‐sized mammals from Lebu Natural Protected Forest, Southwest Showa, Ethiopia

Abstract: This study was conducted to determine the species composition and diversity of medium and large‐sized mammals from Lebu Natural Protected Forest, Ethiopia. Surveys were conducted to record mammals through direct observation and indirect evidence from three habitat types, namely: natural forest, bushland, and riverine forest. A total of 15 mammalian species were recorded. The species recorded were Papio anubis, Chlorocebus aethiops, Tragelaphus scriptus, Canis aureus, Crocuta crocuta, Panthera pardus, Procavia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
4
15
2
Order By: Relevance
“…The species index of the diversity of the study area showed higher species richness (H = 2.56; 1-D = 0.8968) than to study conducted by Qufa and Bekele (2019) in the Lebu natural protected forest, Ethiopia (H = 2.119; 1-D = 0.8167). The grassland habitat is characterized by greater species richness and Shannon diversity index, and vice versa for wetland habitats.…”
Section: Diversity Index Of the Landscapecontrasting
confidence: 60%
See 4 more Smart Citations
“…The species index of the diversity of the study area showed higher species richness (H = 2.56; 1-D = 0.8968) than to study conducted by Qufa and Bekele (2019) in the Lebu natural protected forest, Ethiopia (H = 2.119; 1-D = 0.8167). The grassland habitat is characterized by greater species richness and Shannon diversity index, and vice versa for wetland habitats.…”
Section: Diversity Index Of the Landscapecontrasting
confidence: 60%
“…The conservation status of each species was also identified based on the IUCN Red List (IUCN, 2021). An individual-based rarefaction method was used to estimate species richness and abundance in habitat types and seasons (Legese et al, 2019;Qufa & Bekele, 2019). Similarities in species composition among habitats were presented using Venn diagram.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations